2019
DOI: 10.1177/0267323119886164
|View full text |Cite
|
Sign up to set email alerts
|

Aware Migrants: The role of information campaigns in the management of migration

Abstract: Taking as a starting point studies on the biopolitics of bordering, as well as media studies, this article explores how information campaigns deter potential migrants and refugees from leaving their countries depict them in very specific ways, operating as ‘new bordering practices’ that are in conjunction with extraterritorial border policies. This article probes this question through the example of a specific information campaign – Aware Migrants (2016) – funded by the Italian Government and managed by Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 21 publications
1
28
0
2
Order By: Relevance
“…The papers focus on major immigration countries and on migration pathways between them and source countries. Ten of the selected articles focus on EU member states as countries that launched migration‐information campaigns (Bartels, 2017 ; Brekke & Thorbjørnsrud, 2018 ; Fiedler, 2020 ; Gazzotti, 2019 ; Hartig, 2017 ; Heller, 2014 ; Musarò, 2019 ; Oeppen, 2016 ; Rodriguez, 2019 ; van Bemmel, 2020 ), whereas six papers engage with Australia’s deterrence messaging and Overseas Public Information Campaigns (OPICs) (Fleay et al., 2016 ; Hartig, 2017 ; Hightower, 2013 ; Marczuk, 2016 , Richardson, 2010 ; Watkins, 2017 ). Only two papers look at migration‐awareness‐raising campaigns from the USA (Kosnick, 2014 ; Williams, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The papers focus on major immigration countries and on migration pathways between them and source countries. Ten of the selected articles focus on EU member states as countries that launched migration‐information campaigns (Bartels, 2017 ; Brekke & Thorbjørnsrud, 2018 ; Fiedler, 2020 ; Gazzotti, 2019 ; Hartig, 2017 ; Heller, 2014 ; Musarò, 2019 ; Oeppen, 2016 ; Rodriguez, 2019 ; van Bemmel, 2020 ), whereas six papers engage with Australia’s deterrence messaging and Overseas Public Information Campaigns (OPICs) (Fleay et al., 2016 ; Hartig, 2017 ; Hightower, 2013 ; Marczuk, 2016 , Richardson, 2010 ; Watkins, 2017 ). Only two papers look at migration‐awareness‐raising campaigns from the USA (Kosnick, 2014 ; Williams, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…They also revealed that they used the phones to communicate with friends and members of families abroad, to keep connected with other migrants who were in the process of migrating and, some, to communicate with traffickers to get route information and information about destination country. The point to make out of this is that information campaigns aimed at dissuading migrants from engaging in irregular migration (Brekke & Thorbjørnsrud, 2018;Musarò, 2019;Nieuwenhuys & Pécoud, 2007) may not only carry similar information to what the migrants are already exposed and fail to discourage them from migrating. But migrants have access to other information sources too.…”
Section: Deterring Irregular Migration To Eu Countries and Informatiomentioning
confidence: 99%
“…States and intergovernmental bodies also seek to govern how people think about migration through information campaigns (Brachet, 2016; Fleay et al., 2016; Heller, 2014; McNevin et al., 2016; Musarò, 2019; Nieuwenhuys and Pécoud, 2007; Oeppen, 2016; Pécoud, 2010; Schloenhardt and Philipson, 2013; Watkins, 2017a; Williams, 2019). Such campaigns date to at least the 1980s when the UNHCR used them in Cambodia and Vietnam (United Nations, 1992: 715).…”
Section: Migration Managementmentioning
confidence: 99%